New retting method of cassava roots improve sensory attributes of Bobolo and Chikwangue in Central Africa: an approach through just about right (JAR) test - ZE, Nardis NKOUDOU; ENGAMA, Marie-Joseph MEDZEME; NGANG, Jean Justin ESSIA (Emirates Journal of Food and Agriculture, 2021)
Aim: the aim of this study was to determine sensory profile, through the use of just-about-right (JAR) scales and penalty analysis, of Bobolo and Chikwangue from the cassava roots fermented with previously cassava-fermented chips powder (PCFCP). Furthermore, retting time, cyanide content and pasting properties of retted roots were evaluated. Methods: for that, two samples of Bobolo and Chikwangue obtained from two cassava retting methods were studied: a control made from the retting without PCFCP and a product made from retting with PCFCP. Results: retting time was carried out in 48 hours less with PCFCP and 60% of cyanide reduction more than control. No major modifications occurs in pasting properties of paste fermented with PCFCP. The sensory analysis indicated high levels of acceptability for products made from retting with PCFCP. The penalty analysis showed that attributes “too sour” and “too much fermented odor” affected the acceptability of the Bobolo from retting without PCFCP signiﬁcantly. Conclusion: fermentation of cassava through the use of PCFCP is suitable to improvement of sensory characteristics of fermented cassava by-products.